PELATIHAN PENGOLAHAN BATANG PISANG MENJADI “GEDEBOG CRISPY” DIKAMPUNG SERMAYAM - yosefina mangera; Wahida Wahida; Nurhening Yuni Ekowati; Rosmala Widjijastuti; Indah Widanarti (Musamus Devotion Journal, 2022)
One of the impacts of the spread of covid 19 for the community is the decline in the economic life of the people affected by covid 19. Efforts to revive the economy of the community is done by providing training to the community to produce processed food products that have economic value. One of the most popular processed food products today is banana stem chips. Banana stem chips are processed from the midrib of banana stems, which so far have not been widely used by the community as food. Merauke is an area with an abundance of banana plant diversity, one of which is in Sermayam Village. The PKK women's group in Sermayam Village is one of the community groups that are both targets and partners in this service activity. Partners involved in this service activity are PKK women in Sermayam Village. This training activity aims to increase knowledge and skills to process processed food products from materials available in the local area. With this activity partner members are given training to process banana stems into banana stem chips so that they become more economically valuable. Partners are also given training to package attractive products so that their processed products can be accepted by the market. Seeing the enthusiasm of partners in this activity, partners are expected to increase their productivity so that they are more empowered and independent.